Measuring Traditional Arts' Influence on the Creative Economy: A Study in Desa Tegal Harum - Fariz Antonius Azhari; Aziman, Muhammad Fauzan; Siregar, Yoan Berliana (Yayasan Literasi Sains Indonesia, 2025)
This study examines the influence of traditional arts on the development of the creative economy in Desa Tegal Harum. Using a quantitative approach, data were collected from 150 traditional artists through structured questionnaires. The research employs multiple linear regression analysis to measure the impact of traditional arts on economic growth. The findings reveal a significant positive relationship between traditional arts and the creative economy (R² = 0.67, p < 0.05), indicating that cultural heritage plays a crucial role in fostering sustainable economic development. The study contributes to the creative economy literature by providing empirical evidence on the economic value of traditional arts in rural contexts and establishes a quantitative framework for measuring cultural assets' economic impact. Additionally, it identifies critical intervention points—market accessibility and financial mechanisms—that can optimize traditional arts' contribution to local economies. These insights provide actionable implications for policymakers and stakeholders in developing targeted programs to enhance traditional arts' integration into sustainable economic development models.